Erratum to "Relevance of the antibody response against human immunodeficiency virus type 1 envelope to vaccine design". - Parren, P; Gauduin, M; Koup, R; Poignard, P; Sattentau, Q; Fisicaro, P; Burton, DR (1997)
Understanding the antibody response in HIV-1 infection is important to vaccine design. We have studied the antibody response to HIV-1 envelope at the molecular level and determined the characteristics of neutralizing and non-neutralizing antibodies. These antibodies were isolated from phage display libraries prepared from long-term seropositive asymptomatic individuals. The HIV-1 envelope is presented to the immune system in several antigenically distinct configurations: unprocessed gp160, gp120 and gp41 subunits and native envelope, each of which may be important in eliciting an antibody response in HIV-1 infection. The antibodies tested characteristically had poor affinities for native envelope as expressed on the surface of virions or infected cells, but had high affinities against non-native forms of HIV-1 envelope (viral debris). An exceptionally potent neutralizing antibody in contrast, bound native envelope with equivalent or somewhat higher affinity than this. This indicates that the antibody response in HIV-1 infection is principally elicited by viral debris rather than virions, and that these antibodies bind and neutralize viruses sub-optimally. Potential vaccines should be designed to elicit responses against native envelope.